Perilaku Dan Musuh Alami Kupu Endemik Sulawesi Papilio blumei: Acuan dalam Konservasi - ALIAS, SULFIANTO; SOESILOHADI, RC HIDAYAT (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2015)
Papilio blumei is an endemic butterfly of Sulawesi and especially in Bantimurung Bulusaraung National Park. This research was to observed of the behaviour and natural enemies of P. blumei in Bantimurung Bulusaraung National Park. The behaviour of the insect were mating, foraging, competiting, ovipositing and mud-puddling. Life table was used for analysis of mortality factors, therefore the number of mortality was analyzed by key-factors formulation. The result indicated that mating strategies is patrolling. Foraging activity of the sixth instar was the highest compared to the other instars and the lowest one activity of the prapupa stadium of P. blumei. Nectar host plants for the imago of butterfly were Sarcosephalum latifolius and Eugenia sp. There was Scudderia sp. as an interspesific competitor for larval P. blumei. The intraspesific competitor of the imago stage was male of P. blumei. Female P. blumei laid eggs on abaxial leaf E.hupehensis and the eggs hatched after six days. The larva of P. blumei has a overheating behaviour and the adults has a mud puddling. The natural enemies of P.blumei is Trichogramma sp., with k value = 0.381, Pteromalus sp., with k value = 0.125 and Formica sp., with k value = 0.096.